Gemeinsames Schreiben in der Fremdsprache: Muster, Kreativität und das Glück des Autors - Schindler, Kirsten (Glottodidactica, 2000)
The following article aims at examining the question in how far the text patterns influences the text production process. In an experimental study, German and Polish Students of French were asked to write a letter of application for a stage at the French enterprise Danone in groups of two. The groups could be distinguished due to their state of knowledge concerning the conventions of a typical French letter of application. In the article, I will show the different states from their text product. Besides, I will then ask what this knowledge, or the lack of it, may mean for the text production process. At the end, the article will focus on a discussion concerning the question of teaching writing in L2 and the idea of providing foreign language student with text patterns for different communicative tasks.